Synthesis of Biaryls by Decarboxylative Hiyama Coupling. Issue 14 (21st April 2015) - Katayev, Dmitry; Exner, Benjamin; Gooßen, Lukas J.
Abstract A trimetallic palladium/copper/silver system has been developed that allows the decarboxylative Hiyama coupling of ortho‐substituted aryl carboxylates with trialkoxyarylsilanes to give the corresponding biaryls. The cross‐coupling is catalyzed by a Pd/N‐heterocyclic carbene complex with silver carbonate aiding its reoxidation. Copper(II) fluoride acts as decarboxylation catalyst, stoichiometric oxidant, and fluoride source. The scope of the protocol is demonstrated by 22 examples, among them aryl halides suitable for further coupling, and the synthetic utility of the products is illustrated by their conversion into carbazoles and 1H‐indazoles.